The 2D Geometry Concepts at Al-Mashun Great Mosque: An Ethnomathematics Exploration - Havidah Adawiyah Hasibuan; Rusi Ulfa Hasanah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2022)
This research aims to identify the elements of mathematics, especially two-dimensional geometry concepts in Al-Mashun Great Mosque's building, to be implemented as a source of learning mathematics in the classroom. This research is descriptive-qualitative with an ethnographic approach. The main instrument in this research is a human instrument. Data were obtained from two interviewees, observations, and documentation. Data were analyzed by Spradley’s design: domain analysis, taxonomy, compatibility, and cultural themes. The research results show the elements of the plane figure in the Al-Mashun Great Mosque like triangles, quadrilaterals, octagons, polygons, and circles. These findings indicate that the Al-Mashun Great Mosque can be used in developing learning material like student worksheets or ethnomathematics-based textbooks.